Organocatalytic Enantioselective Friedel–Crafts Alkylation/Lactonization Reaction of Hydroxyindoles with Methyleneoxindoles. Issue 5 (13th December 2017) - Xiao, Mengjie; Xu, Dengfeng; Liang, Weihong; Wu, Wenyu; Chan, Albert S. C.; Zhao, Junling
Abstract: Functionalization of the indole benzene ring was achieved by using an organocatalytic enantioselective Friedel–Crafts alkylation/lactonization reaction of hydroxyindoles with a variety of substituted methyleneoxindoles. This reaction was applicable to indoles substituted with the hydroxy group at different positions of the benzene ring, and the corresponding pyrrolodihydrocoumarins were obtained in moderate to high yields (37–99%) with high stereoselectivities (up to 99% ee and >20:1 dr ) in most cases. A scale‐up reaction and derivatization of the representative products were also carried out to investigate the usefulness of this protocol. Abstract :